EDUKASI PEMANFAATAN POOLED SERA SEBAGAI BAHAN KONTROL ALTERNATIF UNTUK PEMANTAPAN MUTU INTERNAL DI LABORATORIUM - Bastian; Ulva, Maria (Universitas Mataram, 2024)
Quality control is a series of checks performed to evaluate the testing process. Increased automation in the clinical laboratory field has increased the need for QC materials for laboratory performance monitoring. One of them is in the Clinical Chemistry laboratory where before conducting an examination, calibration of equipment must be carried out using commercial control materials. Commercial control serum can be purchased at a high price. Thus, it requires homemade alternative control materials in the form of pooled sera. The purpose of the activity is to provide knowledge about the importance of utilizing pooled sera as an alternative control material for strengthening internal quality in the laboratory. The activity method used is socialization and education through poster media with the aim of increasing knowledge and understanding in officers about the importance of utilizing pooled sera as an alternative control material for strengthening internal quality in the laboratory. There is an understanding and improvement in the results of education on laboratory staff with a pretest value of 45.75 and a posttest of 85.83. Laboratory RSUD Kayuagung have understood the utilization of pooled sera as an alternative control material for internal quality assurance in the laboratory.